THE ENVIROMENTAL LAW AS INSTRUMENT FOR EFETIVAÇÃO OF THE HUMAN RIGHTS, IN CAMAÇARI/BA - Oliveira da Silveira, Thiago (Extensão em Foco, 2013)
The present work has as objective to present the enviromental law under the perspective of the human rights and it’s potentiality for the social transformation. The concern of the people with the environment is visible, with what the communities and the government are making to reduce the environmental damages, which affects the place where we live. Not less important, however not yet pacified in the native doctrine and jurisprudence, it is the agreement of the existing relation between interdependent rights, which are, the human rights and enviromental laws, necessary ones to the others so their efficiency can be regulated. In regards to the access to the environmental information, the lack reveals evident, in the city of Camaçari/BA, relative data to the ambient question and the preservation of the environment, what leads to a incongruity, face to the municipal district necessity to revert the process of environmental degradation which it coexists. Finally, it’s important to mention the humanistic proposal of the University of the State of the Bahia (UNEB), Campus XIX, of social transformation through legal education, research and extension, from the observation of the political-social-environmental reality in which it is inserted.